2007
DOI: 10.1254/jphs.fp0070247
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Quercetin and Rutin on Spatial Memory Impairment in an 8-Arm Radial Maze Task and Neuronal Death Induced by Repeated Cerebral Ischemia in Rats

Abstract: Abstract. In order to determine the differential effects of flavonoids on cerebral ischemia, we investigated the effects of (−)-epigallocatechin gallate (EGCG), catechin, rutin, and quercetin on spatial memory impairment and neuronal death induced by repeated cerebral ischemia in rats. Both rutin and quercetin (50 mg / kg × 2) improved spatial memory impairment in the 8-arm radial maze task and neuronal death in the hippocampal CA1 area; however, catechin (200 mg / kg × 2) and EGCG (50 mg / kg × 1) did not. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
129
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(134 citation statements)
references
References 24 publications
3
129
1
1
Order By: Relevance
“…Furthermore, rutin and its analogues, such as epigallocatechin-3-gallate (EGCG) and quercetin, act as efficient radical inhibitors. They have also been reported to rescue spatial memory impairment in rats with ischemia-reperfusion-induced cerebral injury (Pu et al, 2007). Rutin was also noted to decrease mitochondrial TBARS (Gupta et al, 2003) and to attenuate morphological damage and ischemic apoptosis (Khan et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, rutin and its analogues, such as epigallocatechin-3-gallate (EGCG) and quercetin, act as efficient radical inhibitors. They have also been reported to rescue spatial memory impairment in rats with ischemia-reperfusion-induced cerebral injury (Pu et al, 2007). Rutin was also noted to decrease mitochondrial TBARS (Gupta et al, 2003) and to attenuate morphological damage and ischemic apoptosis (Khan et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Another study showed that the administration of green tea EGCG 10 mg/kg daily for 4 weeks post intracerebroventricular streptozotocininduced dementia can improve the cognitive abilities in Wistar rats assessed with MWM (Biasibetti et al, 2013). However, these results shows a contradiction to an earlier research showing that the administration of green tea EGCG at a dose of 50 mg/kg BW fail to improve spatial memory as well as repair damaged brain neurocells in BALB/c mice with recurrent induction (Pu et al, 2007). The different results could have been due to the different duration of the extract.…”
Section: Discussionmentioning
confidence: 79%
“…Some studies indicate that epigallocatechin-3-gallate (EGCG), main polyphenol in green tea; have antioxidant, antiinflammatory, anticancer, and neuroprotective effect (Lee et al, 2013;YK Lee et al, 2009;Mandel et al, 2008;Miao et al, 2009). However, a study stated that EGCG or green tea extract at a certain dose does not have a significant effect on cognitive function, oxidative stress, or neuroinflammation status (Pu et al, 2007;Flores et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11) Phenolic compounds supposedly attenuate β-amyloid-induced neurotoxicity 12,13) and cerebral ischemia-induced neuronal death. 14) The acorn, Quercus acutissima Carrutthers, is the nut of the oaks and their close relatives. Acorn extract contains phenolic compounds, which are hydrolysable tannins that contain gallic acid, digallic acid and gallotannin.…”
mentioning
confidence: 99%